An observational study of incidence of urological intervention in patients of renal colic with normal and abnormal ultrasound study - Joshi, Ankit; Srivastava, Shirish (International Surgery Journal, 2018)
Background: Renal colic is a common presentation that affects millions people annually. Although ultrasonography has lower sensitivity and specificity in diagnosing urolithiasis compared to CT, it is an alternative imaging modality that does not expose the patient to ionizing radiation. By this observational study an attempt has been made to know the incidence of urological intervention in suspected renal colic patients with normal USG findings, so as to decreasing the number of CT scans and associated ionizing radiation in patients with suspected renal colic. Methods: This was an observational study involving adult patients presenting to the Trauma and Emergency Care Department in Shree Krishna Hospital with suspected renal colic over a 12-months period. Renal ultrasonography was performed in suspected renal colic patients, and the results were categorized into three mutually exclusive groups: normal, suggestive of ureterolithiasis, or visualized ureteric stone. Patients were followed up to see if patients received urological intervention. Results: Of 132 patients enrolled, 16 (12.12%) were classified as normal; none of these patients underwent urologic intervention. 62 (46.92%) USG results were classified as suggestive of ureterolithiasis, and one (1.61%) patient received urologic intervention. A total of 54 (40.91%) USG results were classified as visualized ureteric stone, and 24 (44.45%) patients had urologic intervention. The rate of urologic intervention was significantly lower in those with normal USG results (p <0.001) than in those with abnormal findings. Conclusions: A normal renal ultrasonography predicts a low likelihood for urologic intervention for adult patients with suspected renal colic.